Anti-high-mobility group box-1 (HMGB1) mediates the apoptosis of alveolar epithelial cells (AEC) by receptor of advanced glycation end-products (RAGE)/c-Jun N-terminal kinase (JNK) pathway in the rats of crush injuries - Bin-Fei Zhang; Wei Song; Jun Wang; Peng-Fei Wen; Yu-Min Zhang (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Objectives The lung injury is often secondary to severe trauma. In the model of crush syndrome, there may be secondary lung injury. We hypothesize that high-mobility group box 1 (HMGB1), released from muscle tissue, mediates the apoptosis of alveolar epithelial cells (AEC) via HMGB1/Receptor of advanced glycation end-products (RAGE)/c-Jun N-terminal kinase (JNK) pathway. The study aimed to investigate how HMGB1 mediated the apoptosis of AEC in the rat model. Methods Seventy-five SD male rats were randomly divided into five groups: CS, CS + vehicle, CS + Ethyl pyruvate (EP), CS + FPS-ZM1 group, and CS + SP600125 groups. When the rats CS model were completed after 24 h, the rats were sacrificed. We collected the serum and the whole lung tissues. Inflammatory cytokines were measured in serum samples. Western blot and RT-qPCR were used to quantify the protein and mRNA. Lastly, apoptotic cells were detected by TUNEL. We used SPSS 25.0 for statistical analyses. Results Nine rats died during the experiments. Dead rats were excluded from further analysis. Compared to the CS group, levels of HMGB1 and inflammatory cytokines in serum were downregulated in CS + EP, CS + FPS-ZM1, and CS + SP600125 groups. Western blot and RT-qPCR analysis revealed a significant downregulation of HMGB1, RAGE, and phosphorylated-JNK in CS + EP, CS + FPS-ZM1, and CS + SP600125 groups, compared with the CS groups, excluding total-JNK mRNA. Apoptosis of AEC was used TUNEL to assess. We found the TUNEL-positive cells were downregulated in CS + EP, CS + FPS-ZM1, and CS + SP600125 groups. Conclusion The remote lung injury begins early after crush injuries. The HMGB1/RAGE/JNK signaling axis is an attractive target to abrogate the apoptosis of AEC after crush injuries.